Pemodelan Arsitektur Enterprise Perguruan Tinggi untuk Peningkatan Layanan Pendidikan pada AMIK HASS Bandung : - - MU'MININ, AYI MI'RAZUL; Rohmanto, Ricky; Pradestiawati, Dea (Jurnal Dimamu, 2025)
This study was conducted to model the enterprise architecture of AMIK HASS Bandung in order to improve the effectiveness of its educational services. The study was motivated by the use of information systems that previously operated in a fragmented manner, were not integrated, and were not aligned with institutional objectives. These conditions led to inefficiencies in business activities and academic services. To address these issues, the study employed the Enterprise Architecture Planning (EAP) approach because it provides a structured framework for developing data, application, and technology architectures that are aligned with business needs and support comprehensive and systematic information system planning. The modeling process was carried out through several stages, including planning initiation, business modeling, enterprise surveys, analysis of current systems and technologies, and the development of data architecture, application architecture, and technology architecture. The results produced an enterprise architecture design consisting of key data entities, application requirements to support business functions, the necessary technology platforms, and an implementation roadmap to guide future information system development. The proposed enterprise architecture provides a comprehensive view of organizational information needs and business processes, making it a suitable foundation for developing an integrated information system that aligns with institutional strategies.